Institutionally Adopted Perioperative Blood Management Program Significantly Decreased the Transfusion Rate of Patients Having Primary Total Hip Replacement Surgery - Hargita Dömötör; Ádám L. Varga; Róbert Sződy; Ferenc Tóth; Gábor Nardai (Advances in Orthopedics)
Perioperative transfusion in patients undergoing orthopedic surgery increases the number of postoperative complications. Thus, we have introduced an institution-tailored perioperative blood management program (PBM) to decrease the amount of blood transfused in patients going through primary total hip replacement (THR) surgery. We have conducted a before-after observational cohort study in two predetermined observational periods. Demographic and clinical data, ASA scores, laboratory parameters, features of surgical procedure, and anesthesia were registered. Parameters of perioperative fluid administration, transfusion rate, and postoperative complications were also assessed. One hundred patients in the first and 108 patients in the second observational period were enrolled. Eventhough the ratio of posttraumatic THR procedures increased (9% vs. 17%), the PBM protocol has been utilized effectively and a significant decrease in perioperative blood transfusion rate has been observed (61% vs. 21%). The abolishment of routine preoperative LMWH prophylaxis (90% vs. 16%), intraoperative use of tranexamic acid (10% vs. 84%), and the encouraged exploitation of our postoperative observational facility (5% vs. 39%) were abided by our colleagues. Patients still requiring transfusion had lower preoperative hemoglobin levels (129 vs. 147 g/l), scored higher in ASA (ASA III: 46% vs. 19%), and more often presented postoperative hypotension (40% vs. 7%), oliguria (23% vs. 5%), and infections (9% vs. 2%). We conclude that the individualized perioperative blood management protocol was successfully implemented and yielded a lower transfusion rate and better outcomes. Our study suggests that a partial, institution-tailored PBM program may be suitable and beneficial in countries where the modalities of perioperative blood management are limited.